The Effect of Leadership Towards the Performance of MSME Employees in Cirebon Regency - Wenty Febrianti; Budiman Abdulah (Publikasi Indonesia, 2022)
In Indonesia, MSMEs play an important role in increasing employment, contributing to Gross Domestic Product (GDP) and providing a safety net, especially for those suffering from economic and financial crises. The Indonesian government has realized the importance of the presence of MSMEs in Indonesia, including through the establishment of a special platform under the Ministry of Cooperatives and Small and Medium Enterprises. This research aims to determine and analyze the influence of leadership on the performance of MSME employees in Cirebon Regency. The method used in this research is regression analysis with path diagrams, by testing the outer model and the inner model using SmartPls. The sampling technique in this study uses the Slovin formula so that the number of samples in this research is 280 employees who work in the MSME sector in Cirebon Regency. The results of the study indicate that leadership has an influence on the performance of MSME employees in Cirebon Regency. so that the managerial implications that must be carried out by leaders in terms of improving employee performance are increasing the role of leaders in terms of innovation, and motivating employees and paying attention to the welfare of their employees.